Classification of EEG based task on colour visualization and colour imagery - Purushothaman, Divakar (School of Mechatronic Engineering, 2012)
This thesis discusses the development of colour perception based BMI using non invasive method for the differentially enabled people. The purpose of this research is to develop a simple BMI system using colour perception for the differentially enabled community.